The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1097/ico.0b013e31820129fd
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Study of Expulsive Hemorrhages in 3 Patients With Infectious Keratitis

Abstract: This is the first recorded case of Capnocytophaga keratitis in Japan. Patients with dementia may develop severe ocular complications after infectious keratitis because of their inability to communicate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…In one large case series of Capnocytophaga keratitis patients, 50% of affected eyes required enucleation for corneal perforation, progression to endophthalmitis, or vision loss with uncontrollable pain. Similar to some of the dogs described in this report, Capnocytophaga keratitis may progress rapidly to dramatic corneal perforation and expulsive ocular hemorrhage in human patients . The destructive nature of corneal Capnocytophaga infections is attributed to the elaboration of several proteases, toxins, and virulence factors that induce severe necrotizing inflammation and contribute to evasion of local host immunity .…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In one large case series of Capnocytophaga keratitis patients, 50% of affected eyes required enucleation for corneal perforation, progression to endophthalmitis, or vision loss with uncontrollable pain. Similar to some of the dogs described in this report, Capnocytophaga keratitis may progress rapidly to dramatic corneal perforation and expulsive ocular hemorrhage in human patients . The destructive nature of corneal Capnocytophaga infections is attributed to the elaboration of several proteases, toxins, and virulence factors that induce severe necrotizing inflammation and contribute to evasion of local host immunity .…”
Section: Discussionsupporting
confidence: 67%
“…Capnocytophaga keratitis in human patients is an uncommon infection associated with an aggressive clinical nature and generally poor outcome . In one large case series of Capnocytophaga keratitis patients, 50% of affected eyes required enucleation for corneal perforation, progression to endophthalmitis, or vision loss with uncontrollable pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four days after presentation, the patient developed a Seidel positive inferior paracentral perforation requiring an emergency glue procedure (Figure 1A, middle). As sensitivities for this rare pathogen require send-out evaluation, a review of prior Capnocytophaga case reports 13 suggested treatment with topical clindamycin. Compounded clindamycin 5% was initiated hourly.…”
Section: Case Reportsmentioning
confidence: 99%